Determining the robustness of an interdependent network with a hypergraph model - Gholam Hasan Shirdel; Ameneh Mortezaee (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
The world is included of various entities and complex interdependencies between them that can be appeared in multi-layered networks. It may be the acting of some of these entities depends on the acting of the others such that the failure in one entity may cause failures in a number of others. In this paper we try to model these complex interdependencies in a interdependent network with a directed hypergraph model and then we propose an algorithm to determine minimum number of failure for total failure in the power grid and communication network as a special interdependent network.